The management of housing supply in malaysia : incorporating market mechanisms in housing planning process - Rameli, Alias; Johar, Foziah; Ho, Chin Siong (2006)
The planning mechanisms particularly through development plan and development control and the market system as operated in the housing development process are among the factors that influenced the effectiveness of housing supply system. Previous literature has proven that there was a close interaction between the planning and the market system, particularly with regard to the structure, operation and outcomes of housing supply. Even in the situation of imperfection and failure of the housing market, it becomes a function of planning mechanisms to rectify the failure. In relation to the responsiveness of planning system in managing housing supply, besides focusing on meeting broad housing needs, it is important for the planning system to incorporate the elements of effective demand, housing choice and the market conditions in the housing planning process. This paper aims to clarify the relationship between the planning and the market system in the process of housing supply. It will also highlight the current issues of housing supply in Malaysia and discuss possible method of analysis to be used in evaluating the responsiveness of the planning system in managing housing supply.